Sleep promotion for hospitalised children: Developing an evidence-based guideline for nurses - Elijeshca C. Crous; Natasha North (Curationis, 2021)
Background: Adequate sleep in hospitalised children is important for a variety of physiological and psychological processes associated with growth, development, and recovery from illness and injury. Hospitalisation often prioritises clinical care activities at the expense of age-appropriate sleep. Nurses and the wider healthcare team contribute to this paradox. However, through conscious practice and partnering with mothers, nurses are able to enact change and promote sleep.